Studying higher mental functions: The example of imagination - Zittoun, Tania (Cham etc.: Springer, 2016)
Among the many objects of interest of cultural psychology is imagination. Imagination is a higher function of the mind – that is, it requires the mediation of internalized cultural means. As such, it is both deeply cultural in nature, as well as unique in the way it is experienced by a given person, in a specific time and place. Altogether, it plays a major role in individual and collective change. However, like many others higher functions, it cannot be studied directly: one cannot observe what or how someone is imagining. This is where psychologists have either the choice to give up, or to devise alternative ways to access to imagination. The chapter first defines imagination as sociocultural process. In a second part, it examines methods that have been used, or could be used, to study imagination, especially: case studies, projective tests, lab studies, introspection, autoanalysis, autoethnography, observation, and everyday life enquiry. In the third part, the chapter proposes a synthetic analysis of these techniques, highlighting the specific perspectives they allow for studying imagination. Finally the chapter suggests that such exploration might offer new keys for the study of higher psychological function, that is, for culture in mind and mind in culture.
Keywords: Imagination; methodology; “higher psychological function”; culture; history; cultural psychology